CULTURAL REALITIES AND TRANSLATION STRATEGIES IN THE GERMAN VERSION OF “BOBURNOMA” - Abdurahmonova Dilrabokhon (Western European Studies, 2025)
This article analyzes the translation of cultural realities in the German version of “Boburnoma” by Helmut Dalov. The study explores the types of cultural-specific elements present in the text and identifies the strategies used by the translator to convey these elements to German-speaking readers. The findings contribute to a better understanding of how national and cultural identity is preserved or transformed during translation
Keywords: Linguistic-methodological features; cultural adaptation